Systemic and local vascular inflammation and arterial reactive oxygen species generation in patients with advanced cardiovascular diseases - Sulicka-Grodzicka, Joanna; Szczepaniak, Piotr; Jozefczuk, Ewelina; Urbanski, Karol; Siedlinski, Mateusz; Niewiara, Łukasz; Guzik, Bartłomiej; Filip, Grzegorz; Kapelak, Bogusław; Wierzbicki, Karol; Korkosz, Mariusz; Guzik, Tomasz J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Systemic inflammation may cause endothelial activation, mediate local inflammation, and accelerate progression of atherosclerosis. We examined whether the levels of circulating inflammatory cytokines reflect local vascular inflammation and oxidative stress in two types of human arteries. Methods: Human internal mammary artery (IMA) was obtained in 69 patients undergoing coronary artery bypass graft (CABG) surgery and left anterior descending (LAD) artery was obtained in 17 patients undergoing heart transplantation (HTx). Plasma levels of tumor necrosis factor  (TNF-), interleukin-6 (IL-6) and interleukin-1β (IL-1β) were measured using ELISA, high-sensitivity C-reactive protein (hs-CRP) was measured using Luminex, and mRNA expression of proinflammatory cytokines in the vascular tissues was assessed. Furthermore, formation of superoxide anion was measured in segments of IMA using 5uM lucigenin-dependent chemiluminescence. Results: TNF-, IL-6 and IL-1β mRNAs were expressed in all studied IMA and LAD segments. Plasma levels of inflammatory cytokines did not correlate with vascular cytokine mRNA expression neither in IMA nor in LAD. Plasma TNF- and IL-6 correlated with hs-CRP level in CABG group. Hs-CRP also correlated with TNF- in HTx group. Neither vascular TNF-, IL-6 and IL-1β mRNA expression, nor systemic levels of either TNF-α, IL-6 and IL-1β were correlated with superoxide generation in IMAs. Interestingly, circulating IL-1β negatively correlated with maximal relaxation of the internal mammary artery (r=-0.37, p=0.004). At the same time the mRNA expression of studied inflammatory cytokines were positively associated with each other in both IMA and LAD. The positive correlations were observed between circulating levels of IL-6 and TNF- in CABG cohort and IL-6 and IL-1β in HTx cohort. Conclusions: This study shows that peripheral inflammatory cytokine measurements may not reflect local vascular inflammation or oxidative stress in patients with advanced CVD. Circulating pro-inflammatory cytokines generally correlated positively with each other, similarly their mRNA correlated in the arterial wall, however, these levels were not correlated between the studied compartments.